2016
DOI: 10.1039/c5ra19861e
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of ciprofloxacin and paracetamol by adsorptive stripping voltammetry using copper zinc ferrite nanoparticles modified carbon paste electrode

Abstract: Development of copper zinc ferrite nanoparticles modified carbon paste electrode for the simultaneous determination of ciprofloxacin and paracetamol using adsorptive stripping differential pulse voltammetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…This result is found to be in good agreement with those reported literature [13,46]. Also, it was reported that the number of electrons (n) taking part in the oxidation process can be calculated according to the equation [43] below:…”
Section: The Electrochemical Behaviour Of Actm At Ptà Rgo/gcesupporting
confidence: 91%
See 1 more Smart Citation
“…This result is found to be in good agreement with those reported literature [13,46]. Also, it was reported that the number of electrons (n) taking part in the oxidation process can be calculated according to the equation [43] below:…”
Section: The Electrochemical Behaviour Of Actm At Ptà Rgo/gcesupporting
confidence: 91%
“…EIS has been known as one of the most powerful methods to characterize the surface property of electrodes. The Nyquist plot in EIS measurement normally includes a semicircular portion at high frequency region indicating the limited process of electrons transfer and the diameter of semicircle is equal to the electron transfer resistance (R et ) [43], whereas a linear portion at low frequency relating to the existence of Warburg diffusion resistance [44]. For this reason, EIS was employed in this work to investigate the changes in impedance of the electrodes surfaces.…”
Section: Electrochemical Characterization Of Bare and Modified Electrmentioning
confidence: 99%
“…56,57 Therefore, there is an agreement that CIP is electroactive only under certain particular conditions of pH, buffer and scan rate. 58,59…”
Section: Cpe ¼ 1 ðJuþ P Tmentioning
confidence: 99%
“…Various techniques have already been proposed for the detection of CFX such as potentiometry, high performance liquid chromatography, adsorptive cathodic stripping voltammetry, CV with different modified electrodes,− Spectrophotometry, sensitized lanthanide luminescence, atomic absorption spectrometry, mass spectrometry . However, these method of analysis necessitate convoluted procedure for the preparation of the sample, and consumes more time, high energy.…”
Section: Introductionmentioning
confidence: 99%